Brain Radiation Doses to Patients in an Interventional Neuroradiology Laboratory - Sanchez, R.M.; Vano, E.; Fernández, J.M.; Moreu, M.; Lopez-Ibor, L. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: In 2011, the International Commission on Radiologic Protection established an absorbed-dose threshold to the brain of 0.5 Gy as likely to produce cerebrovascular disease. In this paper, the authors investigated the brain doses delivered to patients during clinical neuroradiology procedures in a university hospital. MATERIALS AND METHODS: The radiation dose delivered to the brain was investigated in 99 diagnostic and therapeutic interventional neuroradiology procedures. Brain doses were calculated in a mathematic model of an adult standard anthropomorphic phantom by using the technical and radiation dose data of an x-ray biplane system submitted to regular quality controls and calibration programs. RESULTS: For cerebral embolizations, brain doses resulted in a maximum value of 1.7 Gy, with an average value of 500 mGy. Median and third quartile resulted in 400 and 856 mGy, respectively. For cerebral angiography, the average dose in the brain was 100 mGy. CONCLUSIONS: This work supports the International Commission on Radiologic Protection recommendation on enhancing optimization when doses to the brain could be higher than 0.5 Gy. Radiation doses should be recorded for all patients and kept as low as reasonably achievable. For pediatric patients and young adults, an individual evaluation of brain doses could be appropriate. AKair kermaCBCTconebeam CTDAPdose-area productICRPInternational Commission on Radiologic ProtectionINRinterventional neuroradiology